Multinational Enterprises, Foreign Knowledge and Host Country - Cieślik, Andrzej (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2012)
In this paper we study how the expansion of multinational enterprises in the host country affects its wages using a general equilibrium factor specific framework for a small open economy with a flexible labor market. We identify three potential effects of MNE activity associated with the transfer of foreign knowledge, diffusion of this knowledge among indigenous firms and the inflow of capital from abroad. We show that the impact of multinational enterprises on wages in the host country depends on differences in capital intensity between multinational and local sectors, the amount of capital transferred to the host country from abroad and the magnitude of knowledge spillovers stemming from multinational activity to indigenous firms.